The construction of post-tensioning slab for high rise buildings / Liyana Rosli - Rosli, Liyana (Universiti Teknologi Mara, Perak, 2016)
The purposed of this report is to explain about the construction post tension slab for high rise buildings at Bandar Baru Bangi. In addition for achieved the requirements standard for BSR 360, I have chosen practical training at Paramount Bounty Sdn Bhd about 4 month started from June until September 2016. I am practical training at there and my position is as assistant site supervisor. Other than that, the purposed of this report are for achieved the requirements standard for BSR 360. The students are need to study the company background and organization chart for the company they are practical, chapter overview for this report, case study at their practical company and the problems and recommendations for. At the end of the semester, the students are able to understand how the company involves in construction works and the flow method statement for construction work. In this chapter are discussing about company background that I am internship for 4 months.